Experimental study of the impact of deck-charge structure on blast-induced fragmentation - Zhixian Hong; Ming Tao; Shurong Feng; Hao Liu; Wenhong Wu; Xudong Li; Shuai Liu (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract The deck-charge structure, also known as axially decoupled charge structure, has been widely applied in open-pit rock excavation to improve blasting performance. However, the relationships between blast-induced fragmentation and deck-charge structures remain not well understood. This paper aims to experimentally investigate the influences of deck ratio, deck position and deck material on blast-induced fragmentation. Concrete specimens with dimension of 400 × 400 × 200 mm3 were used for small-scale single-hole blasting experiments. The dynamic fracturing process under blast loading was recorded with a high-speed camera. Displacement and strain fields were analyzed employing a 3D digital image correlation (DIC) system, and the fragment size distribution (FSD) was quantified through ImageJ, an advanced image-processing tool. The borehole wall pressure (BWP) was monitored through the embedded PVDF gauges within the test specimens. The results indicate that during deck charge blasting, the host concrete undergoes three phases: crushing, further crushing and fracturing, and radial crack development. Fragmentation performance improves within an optimal air-deck ratio range, while excessive ratios lead to poorer fragmentation compared to fully coupled charge blasting. The center deck charge yields the superior fragmentation, followed by double-ends and top deck charges. Water-deck charge generates finer fragmentation than air deck and polyethylene (PE) deck charges. Expanded polystyrene (EPS) deck charge does not facilitate fragmentation but may reduce vibration and limit damage to the remaining rock mass. Based on experiment results, production blasts with fully coupled charge, center air-deck charge and center water-deck charge were performed in an open-pit mine. These field tests revealed that the proposed center deck charge blasting reduced median fragment size by at least 15%, with the center water-deck charge demonstrating superior fragmentation by maximizing explosive energy utilization for rock fracturing.